Computer-supported Environmental Scanning: A Case Study - Yoong, Pak (School of Management Working Papers, 1993)
The identification of strategic options, conducted on a periodic basis, is a critically important aspect of today's modern organisational life. Many business leaders are aware that the clarity with which they view these strategic issues can directly impact on the successful operation of their firms. The current turbulent business environment makes clarity and long range planning difficult. The use of periodic environmental scanning and analysis allows necessary ,adjustments to the overall strategic plan. Researchers have explored the issues of how Computer-Supported Collaborative Work (CSCW) may aid the overall strategic planning process but there has been little attention paid to the processes actually used during environmental scanning and CSCW. This paper analyses the various tasks involved in environmental scanning. It also examines how the tools of CSCW may aid the identification of strategic issues in 'ill-structured' or 'wicked' environmental conditions. A case example, taken from a New Zealand firm involved in a restructuring process, is provided to illustrate the computer-supported environmental scanning approach and to show how information technology can help sorting out strategic planning issues faced by organisations and subunits of,.. organisations.